Economía circular como desarrollo sostenible, reciclaje y medio ambiente en el GAD Municipal del cantón Bolívar, año 2022 - Córdova Ponce, Pierina Judafith (2023)
The main objective of this research was to implement the importance of the circular economy as sustainable development, recycling and the environment in the Municipal Decentralized Autonomous Government in Bolívar canton, year 2022. In addition, different methodologies, techniques and methods were used which served as the basis for the collection and processing of information. Likewise, the activities corresponding to each phase of the investigation were carried out. Therefore, in the first phase the search for bibliographic information of the study variables was carried out, later in the second phase the respective instruments were used such as the interview directed to the recyclers of the canton and to the Head of Environmental Management. Therefore the survey was applied to the citizens of the canton, who were the main source of information collection, with the purpose of finding the problems or shortcomings to be able to give solutions. Finally, in the third phase the pilot plan was proposed thus establishing the necessary strategies that contribute to fulfilling the purpose of the investigation. In this context, it is concluded that the Bolívar canton GAD must apply the pilot plan, where the necessary strategies are established that contribute to fulfilling the purpose of the investigation.